Impact of Shift Work on Nurse Fatigue and Productivity in an Indonesian Inpatient Ward: A Cross-Sectional Study - Sri Rahayu; Andiko Nugraha Kusuma (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Shift work, particularly night shifts, is known to affect the health and productivity of healthcare workers. However, there is limited research on how shift work impacts nurses in low-resource settings, such as secondary hospitals in Indonesia. This study aims to explore the effects of different shift types on nurse fatigue and productivity in Indonesia, filling a critical gap in the literature. A cross-sectional study was conducted with 150 nurses from Rumah Sakit Umum Daerah Deli Serdang (RSUDDS) in Medan, Indonesia. Participants were selected using stratified random sampling based on their shift types (morning, evening, night). Fatigue was measured using the Nurse Fatigue Scale (NFS) and Pittsburgh Sleep Quality Index (PSQI), while productivity was assessed through both self-reports and objective task completion data. Statistical analyses included one-way ANOVA, multiple regression, and effect size calculations (Cohen's d). Night shift nurses reported significantly higher fatigue levels (mean NFS = 32.4) and lower productivity (mean self-reported productivity = 6.1) compared to morning (NFS = 28.3; productivity = 7.2) and evening shift nurses (NFS = 30.1; productivity = 6.9). The differences were statistically significant (p < 0.01). Cohen's d for the comparison of fatigue between night and morning shifts was 0.68, indicating a moderate effect. Multiple regression analysis revealed that fatigue (β = -0.48, p < 0.001), shift type (β = -0.29, p < 0.01), and work environment factors (β = -0.35, p < 0.05) were significant predictors of nurse productivity. Night shifts were strongly associated with higher fatigue and lower productivity among nurses. To mitigate these effects, hospitals should consider implementing policies such as limiting consecutive night shifts and providing structured rest breaks. Further research, particularly longitudinal studies, is needed to explore causal relationships and test scheduling interventions to optimize nurse well-being and performance. Keywords: Shift work, Occupational health, Nurse productivity, Fatigue